Analysing Tax-Benefit Reforms in the Netherlands: Using Structural Models and Natural Experiments - Henk-Wim de Boer; Egbert L. W. Jongen (Institute of Labor Economics (IZA), 2020)
We combine the strengths of structural models and natural experiments in the analysis of tax-benefit reforms in the Netherlands. First we estimate structural discrete-choice models for labour supply. Next we simulate key past reforms and compare the predictions of the structural model with the outcomes of quasi-experimental studies. The structural model predicts the treatment effects well. The structural model then allows us to conduct counterfactual policy analysis. Policies targeted at working mothers with young children generate the largest labour supply responses, but generate little additional government revenue. Introducing a at tax, basic income or joint taxation is not effective.
Keywords: C25; C52; H31; J22; 330; tax-benefit reform; natural experiments; structural models; Netherlands